2018
DOI: 10.3390/toxins10010025
|View full text |Cite
|
Sign up to set email alerts
|

Protective and Detoxifying Effects Conferred by Dietary Selenium and Curcumin against AFB1-Mediated Toxicity in Livestock: A Review

Abstract: Aflatoxin B1 (AFB1), among other aflatoxins of the aflatoxin family, is the most carcinogenic and hazardous mycotoxin to animals and human beings with very high potency leading to aflatoxicosis. Selenium is an essential trace mineral possessing powerful antioxidant functions. Selenium is widely reported as an effective antioxidant against aflatoxicosis. By preventing oxidative liver damage, suppressing pro-apoptotic proteins and improving immune status in AFB1 affected animals; selenium confers specific protec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(58 citation statements)
references
References 129 publications
2
56
0
Order By: Relevance
“…Curcumin is a polyphenol commonly composed of three types of curcuminoids, bisdemethoxycurcumin, demethoxycurcumin, and diferuloylmethane, derived from the rhizome of Curcuma longa (Common name: turmeric) famous for its pharmacological and therapeutic properties ( Anand et al, 2008 ). Several reports have documented the anti-inflammatory, anti-oxidative, anti-cancerous, and potent chemotherapeutic properties of curcumin ( Aggarwal et al, 2003 ; Joe et al, 2004 ; Liew and Mohd-Redzwan, 2018 ; Limaye et al, 2018 ; Rauf et al, 2018 ). It has been proved earlier that curcumin is effective against AFB 1 -induced oxidative stress ( Gowda et al, 2009 ; El-Bahr, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Curcumin is a polyphenol commonly composed of three types of curcuminoids, bisdemethoxycurcumin, demethoxycurcumin, and diferuloylmethane, derived from the rhizome of Curcuma longa (Common name: turmeric) famous for its pharmacological and therapeutic properties ( Anand et al, 2008 ). Several reports have documented the anti-inflammatory, anti-oxidative, anti-cancerous, and potent chemotherapeutic properties of curcumin ( Aggarwal et al, 2003 ; Joe et al, 2004 ; Liew and Mohd-Redzwan, 2018 ; Limaye et al, 2018 ; Rauf et al, 2018 ). It has been proved earlier that curcumin is effective against AFB 1 -induced oxidative stress ( Gowda et al, 2009 ; El-Bahr, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…CMN was suggested to have specific cellular pathways for AFB1 detoxification (Muhammad et al, 2018) and p53 downregulation in various tumors like colon (Moos, Edes, Mullally, & Fitzpatrick, 2004) and breast (Hallman et al., 2017) cancers, but scarce data are available for its role in liver or kidney cancers. The mostly known action of CMN is its role in restricting the aflatoxigenic potential of A. flavus , by inhibiting the cytochrome P450 isoenzymes, particularly CYP2A6 isoform; thereby reducing the formation of AFB1‐8,9‐epoxide and other aflatoxin metabolites (Limaye, Yu, Chou, Liu, & Cheng, 2018). Our findings suggest that BTE and CMN showed synergistic effect in protection against not only AFB1‐induced hepatotoxicity (Alm‐Eldeen, Mona, Shati, & El‐Mekkawy, 2015), but also the renal toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…The AFB1‐mediated toxicity in tissues was attributed to the accumulated intracellular ROS, that is, superoxide anion, hydroxyl radical, and H 2 O 2 during the biotransformation of AFB1 by the CYP450 enzyme in liver (Ozen et al., 2009). Relevant studies indicated that AFB1 metabolized by the CYP450, was transformed into exo‐AFB1‐8,9‐epoxide (AFBO), which binds to DNA, proteins, and critical macromolecules within cells exerting a carcinogenic effect (Gross‐Steinmeyer & Eaton, 2012), and that effect could be blocked by curcumin (Limaye et al., 2018). LPO induced by the AFB1 leads to alteration of the membrane structure and enzyme activity, as a result of oxidizing the AFB1 into AF‐8‐9‐epoxide, a highly toxic reactive intermediate, by CYP450 (Niki, Yoshida, Saito, & Noguchi, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…[ 42 ] and Limaye et al . [ 43 ]. Kieliszek and Błażejak [ 44 ] stated the importance of Se as micronutrients, as it helps in the protection from hydrogen peroxide, detoxification of heavy metals, enhancement of production and performance, and improvement of the immune system.…”
Section: Discussionmentioning
confidence: 99%